THE SECOND KARABAKH WAR: A CRITICAL TURNING POINT IN AZERBAIJAN–TÜRKİYE RELATIONS - Guliyeva, Rukhsara Bahtiyar (Вісник гуманітарних наук, 2025)
Karabakh has caused a problem between states located in the region or having an interest in it and Azerbaijan due to its historical essence, natural resources and strategic geographical position throughout history. Karabakh, a region inhabited historically by the Turkish-Muslim population, has been attacked by armed Armenian gangs since the beginning of the 20th century. The main reason for this attack was the desire to realize the idea of "Greater Armenia from sea to sea". Since 1988, the Karabakh problem has entered a new direction, and the occupation process by Armenian has begun. This process accompanied by expulsion, massacre, genocide, occupation was temporarily stopped by the Bishkek protocol dated May 12, 1994, a ceasefire was declared, and with the military operations started on September 27, 2020, it went down in history as the First Karabakh War. The Second Karabakh War, which took place between September 27 and November 10, 2020, ended with the victory of Azerbaijan. The Karabakh problem has always been a priority topic of Azerbaijan-Türkiye relations. The main problem of Azerbaijan, which declared its independence on the eve of the collapse of the USSR in 1991, was the Karabakh issue. Türkiye was the first country that recognized our independence and declared Armenia, which occupied our lands, an occupying state and closed its borders with it. The second Karabakh war raised the relations that began to intensify with the independence of Azerbaijan to the highest level of strategic partnership and created an important intersection and turning point in the relations between the two countries, which are based on solid foundations.